2023
DOI: 10.1037/cfp0000200
|View full text |Cite
|
Sign up to set email alerts
|

Maybe, maybe not: Racial discourse and worldview in interracial relationships.

Abstract: Using a multidimensional understanding of race, the present study investigated whether racial worldview informs the initiation of discussions of race within interracial relationships. Two hundred three individuals in interracial relationships completed measures to assess their perceptions of the intrapersonal, interpersonal, and institutional implications of race and ethnicity and indicated whether they discussed race with their romantic partner. Responses to open-ended questions were coded using consensual qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This conclusion is especially illuminating considering prior research on REW. Mixed-method analyses have indicated that some color-blind types are less likely to discuss race openly with their partner (Brooks et al, 2021a ) and that Multiculturalist types are more likely to discuss issues of systemic racism and efforts to mitigate its impact (i.e., social protest movements; Brooks et al, 2021a ). This is especially encouraging as prior research has found that these conversations can be tense or dismissive of one person's experience (Killian, 2002 ), or even limited to understanding the difference in the race as inherently problematic (Brummett, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This conclusion is especially illuminating considering prior research on REW. Mixed-method analyses have indicated that some color-blind types are less likely to discuss race openly with their partner (Brooks et al, 2021a ) and that Multiculturalist types are more likely to discuss issues of systemic racism and efforts to mitigate its impact (i.e., social protest movements; Brooks et al, 2021a ). This is especially encouraging as prior research has found that these conversations can be tense or dismissive of one person's experience (Killian, 2002 ), or even limited to understanding the difference in the race as inherently problematic (Brummett, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that a critical and multidimensional understanding of race and racism informs subjective experiences in relationships. Prior research has shown that REW affects what impact individuals believe race has on their interracial relationships as well as what specific topics are discussed (Brooks et al, 2021a , b ). The existing research could not directly assess whether there were impacts of these discussions on relationship functioning, the current study takes a step closer to understanding the implications of these conversations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations